Evaluation of The Attainment of Environmental Goals in Sustainable Growth Regarding Gas Emission and Energy Consumption, as Defined for Poland in the Europe 2020 Strategy - Witkowska-Dąbrowska, Mirosława (Olsztyn Economic Journal, 2018)
In March 2010, the European Commission announced a 10-year strategic plan called ‘Europe 2020 – A strategy for smart, sustainable and inclusive growth’. At the same time, the Polish authorities approved several strategic documents connected with the Lisbon Agenda and the new Europe 2020 Strategy, intended to support the development of RER and the reduction of emissions, mainly of greenhouse gases. The objective of this study has been to assess the indicators of sustainable growth for Poland against the backdrop of these indicators for the European Union. The analysis included indicators related to gas emission and energy consumption in the years 2004, 2010 and 2015. For each indicator, a so-called demonstration assessment value was calculated, which shows by what percentage the value of a given indicator achieved in Poland is better or worse than the average value of this indicator for the European Union member states The study showed positive changes in the individual indicators in 2004–2015.